IT governance maturity in higher education: A study in Brazilian and Portuguese Universities - Bianchi, Isaías Scalabrin (2018)
The use of Information Technology has become prominent in teaching, learning, research, service and management activities in higher education institutions. Such prominent usage has caused a critical dependency on IT that demands adequate IT governance beyond simple and daily IT management. One way of achieving IT governance is through an appropriate set of structure, process and relational mechanisms. We have examined these types of mechanisms in six universities, four in Brazil and two in Portugal. This study was carried out using interviews to assess the level of implementation for seventeen structure, fifteen process and fourteen relational mechanisms. Findings show that the relational mechanisms were the most implemented in these six universities under study. Anyway, from this sample, we are led to the conclusion that IT governance maturity appears quite low in higher education.